The Effect of Project Based Learning on Digital Literacy Skills and Conceptual Understanding in an Online-Based Flipped Classroom Environment - Miftahus Surur; Supiana Dian Nurtjahyani; Agusti Agusti; Indah Yana (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to determine the effect of project-based learning on digital literacy skills and concept understanding in an online-basedflipped classroom environment. Methods used by researchers quantitative research methods. The methodological steps used by researchers are. First, researchers designed a learning design that is in accordance with the concept of PBL and online-based flipped classrooms. The research location is at STKIP PGRI Situbondo. For the population and research sample, researchers used a saturated sample of 105 students. Next, the data will be collected using test instruments. Instrument trials include: validity, reliability, difficulty, and differentiating power and continue with hypothesis testing. The results of this study are based on the results of the analysis and discussion of Project-Based Learning (PBL) learning methods that affect digital literacy skills and concept understanding in an online-based flipped classroom environment with a score of 0. 02 and 0. 03 < 0.05 then it can be concluded that there is an influence of variable X on variables Y1 and Y2. These findings also prove temporarily that PBL is suitable for use in learning through the digital world, in accordance with the main purpose of PBL whichprioritizes constructivist learning which involves the use of classical and digital books and activities in the field.